Analisis Faktor Penghambat Usaha Mikro dan Kecil pada Industri Fashion Hijab di Kota Bandung - Silmi Izdihar; Siska Noviaristanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The fashion creative industry is the 2nd largest business unit in Indonesia, especially the fashion business category in clothing including hijab, which experienced a minimal increase in 2019-2021. Business competition can have an impact on business bankruptcy. So, it is important to create a long-term business strategy for businesses to minimize obstacles when running a business in order to avoid business bankruptcy. The purpose of this study is to determine what are the most dominant or frequent inhibiting factors in the development of micro and small businesses in the hijab fashion industry in Bandung City. This research method utilizes quantitative methods. The data collection technique used a questionnaire given to 105 respondents in Bandung City. The results of this study resulted in five factors inhibiting the development of micro and small businesses in the hijab fashion industry in Bandung City, namely Capital Limitations, Internet Mastery, Management Quality, Human Resource Limitations, and Marketing Difficulties. Limited human resources is the dominant or frequent inhibiting factor in business development. So it is recommended to involve training and continuing education to improve HR skills in the hijab fashion industry, through workshops, partnerships with educational institutions, and joining communities or business associations.